Pengembangan LKPD Berbasis Model SSCS terintegrasi Strategi Meringkas untuk Memberdayakan Berpikir Kritis dan Literasi Sains - Yusnaeni Yusnaeni; Sudirman Sudirman; Aria Rahma Dhanii; Maryanto C. Honin; Maresti Tanaem; Karolina Nau; Susana Jelita (Universitas Negeri Jakarta, 2026)
This innovative worksheet is designed based on the Search, Solve, Create, and Share (SSCS) model integrated with the Summarizing strategy to foster scientific literacy and critical thinking in students. This research aims to produce a worksheet based on the SSCS learning model integrated with the summarizing strategy that is valid and suitable for use in learning. This research is a developmental research and development (R&D) adapting the 4D model by Thiagarajan, Sammel, and Semmel. The research instruments used were an interview guide, expert validation sheet, teacher and student response sheets, and an integrated test instrument for critical thinking and scientific literacy. Data were analyzed descriptively. The resulting worksheet is suitable for use in learning because it meets the criteria for good preparation, namely didactic, constructive, and technical requirements. This product was declared highly valid with a score of 3.78 by media experts and 3.69 by material experts. Student and teacher responses also indicated that this worksheet product was suitable for use, with scores of 90.00% and 95.75%, respectively. Worksheets based on the integrated summarization strategy and the SSCS model can improve students' critical thinking skills and scientific literacy.